Clinical Features and Surgical Treatment of Subretinal Proliferation in Proliferative Diabetic Retinopathy - Wu, Chan; Dai, Rongping; Chen, Youxin; Zhang, Xiao; Chen, Zhe (Frontiers in Medicine, 2022)
Purpose To describe the clinical characteristics, treatments, and prognosis of subretinal proliferation (SRP) in proliferative diabetic retinopathy (PDR) patients. Methods A total of 184 patients (221 eyes) who received vitrectomy for PDR between 2018 and 2021 were retrospectively reviewed. Patients with SRP were further evaluated. The following data were collected from their medical records: demographics, systemic and ophthalmologic findings, and treatment given specifically for SRP. The main outcome measures included the visual acuity (VA), funduscopic examination, and final anatomic success. Results Twelve eyes of eleven patients including seven females and four males with a mean age of 47.64 ± 11.21 years were evaluated. The surgical indication for the patients was mainly tractional retinal detachment (TRD) (100.0%). No retinal break was found preoperatively or intraoperatively. Only one eye (8.3%) had undergone subretinal band removal procedure intraoperatively, and the final anatomical success rate was 100%. Conclusion Subretinal proliferation in PDR was associated with TRD. The retina could reattach successfully after vitrectomy without removal or transection of SRP in most eyes.